Developing a Model for Learning from Movies in a B-School with a Case Study - Kulkarni, Vaibhav (SFIMAR Research Review, 2016)
B-Schools have been screening movies to highlight management concepts such as team work, leadership and motivation. Some institutes even use animated movies as a tool of instruction. While many B-Schools are spending valuable hours in screening such movies, the question of 'how much' is learnt remains unanswered. Some B-Schools take a written feedback on what is learnt from a particular movie, some discuss these points verbally. There are no definite parameters or steps defined and established to analyze the learning from movies which are relevant to a business management classroom. This paper has made an attempt to define and establish some concrete steps and methodology to analyze the learning from movies screened in a management classroom. Thus by merely saying that a student learns the concept of leadership is not enough. It has to go beyond what is 'obvious'. The learning should have enough depth for the student to relate it to the existing surroundings. This paper may help the students and teachers to follow a definite pedagogical structure while using movies as a mode of learning and instruction.